An Identity Capital Model Perspective for Social Entrepreneurship Education - Ilyas, Mohammad Syairozi Dimyathi; Humaira, Aida; Adhha, Nurul; ., Suryaneta (International Journal of Membrane Science and Technology, 2023)
Previous research has highlighted the primary objective of social entrepreneurship as balancing social and commercial purposes. Social entrepreneurs face significant challenges in managing their ventures, and there is a pressing need to equip students with the necessary knowledge and skills to overcome these challenges through social entrepreneurship education. To address this need, the authors propose a curriculum matrix based on the Identity Capital Model to aid students in achieving social entrepreneurship objectives while incorporating the principles of innovation and sustainability. The proposed curriculum matrix was developed based on data collected through semi-structured interviews with successful youth social entrepreneurs. The sample size was determined using data saturation. The authors analyzed the backgrounds, personal experiences, motivations, and difficulties encountered by participants in launching and operating their social enterprises using the Narrative Analysis Theory of William Labov and Joshua Waletzky. The Identity Capital Model was used as a theoretical framework to identify the key factors contributing to the success of youth social entrepreneurs.